2019
DOI: 10.1073/pnas.1906394116
|View full text |Cite
|
Sign up to set email alerts
|

Mapping hole hopping escape routes in proteins

Abstract: A recently proposed oxidative damage protection mechanism in proteins relies on hole hopping escape routes formed by redox-active amino acids. We present a computational tool to identify the dominant charge hopping pathways through these residues based on the mean residence times of the transferring charge along these hopping pathways. The residence times are estimated by combining a kinetic model with well-known rate expressions for the charge-transfer steps in the pathways. We identify the most rapid hole ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 55 publications
(83 reference statements)
0
65
0
Order By: Relevance
“…Indeed, examination of the Tt AA10A structure for potential charge transfer pathways using the programme EHPath shows that a clear and rapid hole-hopping pathway with a mean hole residence time of only 20 ms exists between histidine 1 and tyrosine 3 (10 Å separation). Tyrosine 3 is adjacent (5.3 Å) to the second Cu site, thus providing an efficient charge transfer pathway between the two copper sites [34]. Therefore, given the potential charge transfer pathway between the two copper sites, we investigated whether the second metal site (in our case occupied by copper, although we could not displace the Cu with Fe, Ni, Zn and Mn salts) represents a binding site for a proteinaceous redox partner (the binding of another protein to this site is hinted at by the Strep-tag association with a neighbouring molecule in the crystalline lattice), and we attempted to pull down proteins from the T. turnerae predicted secretome that may stably interact with Tt AA10A using affinity column (StrepTrap HP) immobilised Tt AA10A.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, examination of the Tt AA10A structure for potential charge transfer pathways using the programme EHPath shows that a clear and rapid hole-hopping pathway with a mean hole residence time of only 20 ms exists between histidine 1 and tyrosine 3 (10 Å separation). Tyrosine 3 is adjacent (5.3 Å) to the second Cu site, thus providing an efficient charge transfer pathway between the two copper sites [34]. Therefore, given the potential charge transfer pathway between the two copper sites, we investigated whether the second metal site (in our case occupied by copper, although we could not displace the Cu with Fe, Ni, Zn and Mn salts) represents a binding site for a proteinaceous redox partner (the binding of another protein to this site is hinted at by the Strep-tag association with a neighbouring molecule in the crystalline lattice), and we attempted to pull down proteins from the T. turnerae predicted secretome that may stably interact with Tt AA10A using affinity column (StrepTrap HP) immobilised Tt AA10A.…”
Section: Resultsmentioning
confidence: 99%
“…However, is it possible that the W96/W274 pair is just the beginning of a longer multi-step hole hopping pathway that shuttles oxidative power away from the active site? With seven tryptophans and fourteen tyrosines out of 385 residues per subunit, OxDC contains a large number of potentially redox-active amino acids, similar to other proteins that were shown to have protective electron transfer chains (15). To investigate this question further, we carried out additional hopping pathway calculations to discover electron transfer from either Mn binding site to aromatic residues at the surface of the proteinspecifically Y107, Y228, and Y244, which are partially exposed, as well as to Y283 which has an oxygen atom exposed at the surface (Fig.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…In 2015, Gray and Winkler showed that approximately one third of the protein structures in the PDB database have putative redox chains of three or more residues linked to a surface-exposed tyrosine or tryptophan, and they suggested that hole hopping through these groups may serve as a protection mechanism from oxidative damage (10). More recently, Teo et al (15) developed a kinetic model to describe multi-step hopping transport through proteins. It allowed the theoretical identification of putative hole hopping escape routes in cytochrome P450 monooxygenase (P450 BM3 from Bacillus megaterium), cytochrome c peroxidase (Ccp1 from Saccharomyces cerevisiae), and benzylsuccinate synthase (BSS from Thauera aromatica) (15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10) as the hole donor to be used in model 2. For both kinetic models, we used the EHPath.py code 63 (setting the reorganization energy scaling parameter a to unity 63 ) to nd the fastest charge hopping pathways and to calculate the corresponding s value in the MD snapshots of the WT and Y345C systems selected each ns over the time windows indicated in Fig. 2.…”
Section: Kinetic Modelingmentioning
confidence: 99%